Analysis of extracorporeal membrane oxygenation in trauma patients with acute respiratory distress syndrome: A case series. Issue 1 (January 2022) - Weidemann, Friederike; Decker, Sebastian; Epping, Jelena; Örgel, Marcus; Krettek, Christian; Kühn, Christian; Wilhelmi, Michaela
Background: Thoracic trauma is the most common injury in polytrauma patients. Often associated with the development of an acute respiratory distress syndrome (ARDS), conservative treatment options are very restricted and reach their limits quickly. Objective: Extracorporeal membrane oxygenation (ECMO) is a wellestablished therapy in cardio-thoracic surgery and internal medicine intensive care units. The purpose of this study is to analyse the potential benefit of ECMO therapy in ARDS treatment in polytrauma patients. Design: Retrospective case series. Setting: Level 1 trauma centre, Germany, 04/2011-04/2019. Patients: Nineteen patients with ARDS treated with a veno-venous ECMO system. Main outcome measures: This study focused on the time leading to therapy initiation, the severity of thoracic and overall injury. The Sequential Organ Failure Assessment (SOFA) Score, the Murray Score, the Abbreviated Injury Scale (AIS) 2005 level and the Injury Severity Score (ISS) were analysed. The results were analysed regarding survival and death. Results: The survival rate was 53%. The ISS was the same for survivors and deceased patients ( p = 0.604). Early initiation of ECMO therapy showed a significant trend for survivors ( p = 0.071). The SOFA Score level before ECMO therapy was significantly lower in the survivors than in those who died ( p = 0.035). The AISThorax level for survivors showed a significantly higher score level than the one for deceased patients ( p = 0.05). Conclusion: ECMO therapy in polytrauma patients is a safe and effective option, in particular when used early in ARDS treatment. The overall severity of organ failure determined the likelihood of survival rather than the thoracic trauma itself.